2023
DOI: 10.7189/jogh.13.04078
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cognitive training on domains of attention in older adults with mild cognitive impairment and mild dementia: A meta-analysis of randomised controlled trials

Abstract: Background Attention is essential to daily life and cognitive functioning, and attention deficits can affect daily functional and social behaviour, such as falls, risky driving, and accidental injuries. However, attention function is important yet easily overlooked in older adults with mild cognitive impairment, and evidence is limited. We aimed to explore the pooled effect of cognitive training on domains of attention in older adults with mild cognitive impairment and mild dementia using a meta-analysis of ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Several previous studies have reported that VitD did not affect global cognition, neither improved cognitive functioning on supplementation 13,40,42 . Deficits in attention is a part of aging and it has been found that attention training interventions improved cognitive functioning in individuals with MCI or mild to moderate dementia 57 . VitD deficiency is a well-known biomarker of Attention-Deficit/ Hyperactivity Disorder (ADHD) in children 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have reported that VitD did not affect global cognition, neither improved cognitive functioning on supplementation 13,40,42 . Deficits in attention is a part of aging and it has been found that attention training interventions improved cognitive functioning in individuals with MCI or mild to moderate dementia 57 . VitD deficiency is a well-known biomarker of Attention-Deficit/ Hyperactivity Disorder (ADHD) in children 58 .…”
Section: Discussionmentioning
confidence: 99%